Outcome-based Approach in Teaching Digital Systems Design for Undergraduate Computer and Electronics Engineering Programs - Llorente, C. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The adoption by the Philippine Educational system of the K to 12 program, which puts an additional 2 years in the secondary education of high school students, prompted Higher Educational Institutions particularly offering engineering programs to rewrite the curriculum. With the new curriculum for all engineering programs already at the public consultation stage, the contents of the teaching materials must be adjusted to comply with the Outcome Based Education (OBE). In this work, an outcome-based laboratory manual for teaching digital systems design has been developed, and the approaches used in its adoption are described. Key features of the manual are the tutorials section which introduces VHDL and FPGA as the hardware modeling and implementation tools, and then followed by machine problems which are small projects that can be designed and implemented a team of students up to 5 members. The machine problems after implementation can be reused to develop the term project which has a higher level of complexity. Three ways of administering the course using the laboratory manual in three consecutive academic years are presented. Based on the experience, it is surmised that approach requiring students to devise their own experiments from solving machine problems while integrating the results of the tutorial to the theoretical framework section of the experiment document provided the balance between tutorial-based learning and output-based learning.